Severity of hyperoxia as a risk factor in patients undergoing on-pump cardiac surgery - Jakutis, Gabrielius; Norkienė, Ieva; Ringaitienė, Donata; Jovaiša, Tomas (Acta medica Lituanica, 2017)
Background. Hyperoxia has long been perceived as a desirable or at least an inevitable part of cardiopulmonary bypass. Recent evidence suggest that it might have multiple detrimental effects on patient homeostasis. The aim of the study was to identify the determinants of supra-physiological values of partial oxygen pressure during on-pump cardiac surgery and to assess the impact of hyperoxia on clinical outcomes. Materials and methods. Retrospective data analysis of the institutional research database was performed to evaluate the effects of hyperoxia in patients undergoing elective cardiac surgery with cardiopulmonary bypass, 246 patients were included in the final analysis. Patients were divided in three groups: mild hyperoxia (MHO, PaO2 100–199 mmHg), moderate hyperoxia (MdHO, PaO2 200–299 mmHg), and severe hyperoxia (SHO, PaO2 >300 mmHg). Postoperative complications and outcomes were defined according to standardised criteria of the Society of Thoracic Surgeons. Results. The extent of hyperoxia was more immense in patients with a lower body mass index (p = 0.001) and of female sex (p = 0.005). A significant link between severe hyperoxia and a higher incidence of infectious complications (p – 0.044), an increased length of hospital stay (p – 0.044) and extended duration of mechanical ventilation (p < 0.001) was confirmed. Conclusions. Severe hyperoxia is associated with an increased incidence of postoperative infectious complications, prolonged mechanical ventilation, and increased hospital stay.